Acanthosis nigricans associated with transitional cell carcinoma of the urinary bladder - Gautam K Singh; Debraj Sen; D S Mulajker; M S Suresh (Wolters Kluwer Medknow Publications, 2011)
An elderly man from the region of Ladakh presented with recurrent episodes of lower respiratory tract infection, rapidly progressive Acanthosis nigricans, Acanthosis palmaris and plantar keratoderma. Detailed investigations revealed underlying metastatic transitional cell carcinoma of the bladder. This case is being reported for its rarity in the literature.